intrapartum treatment procedure in two fetuses with airway obstruction - Joohee Lee; Mi-Young Lee; Yeni Kim; Jae-Yoon Shim; Hye-Sung Won; Euiseok Jeong; Byong Sop Lee; Ki-Soo Kim; Woo-Jong Choi; Yoon Se Lee (Korean Society of Obstetrics and Gynecology, 2018)
The ex utero intrapartum treatment (EXIT) procedure was introduced to reduce fetal hypoxic damage while establishing an airway in fetuses with upper and lower airway obstruction. Delivery of the fetal head and shoulders while maintaining the uteroplacental circulation offers time to secure the fetal airway. Here, we report two cases of EXIT procedure for fetal airway obstruction, which were successfully managed with extensive preoperative planning by a professional multidisciplinary team.